DO UNIVERSITY SUPPORT, ENTREPRENEURIAL ATTITUDES, SUBJECTIVE NORMS, AND SELF-EFFICACY INFLUENCE STUDENT ENTREPRENEURIAL INTENTION? - Xevinkeng Xevinkeng; Chrisanty Victoria Layman (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- This study aims to examine the effect of university entrepreneurship support on entrepreneurial intentions which are influenced by the mediating effect of entrepreneurial attitudes, subjective norms, and entrepreneurial self-efficacy in undergraduate students studying in Jakarta and or Tangerang. The sampling technique used is the purposive sampling technique where the respondents were undergraduate students in Jakarta and or Tangerang who have entered their universities for at least one year. The sample used in this study comprises 280 respondents with data collection methods in the form of electronic questionnaires. The data was processed using PLS-SEM descriptive analysis using SmartPLS software. The results showed that university entrepreneurship support had a positive influence on entrepreneurial intentions and attitudes toward entrepreneurship, subjective norms, and self-efficacy. The study also showed a significant mediating effect of attitudes and self-efficacy on the positive relationship of university entrepreneurship support to entrepreneurial intentions. The results of this study contribute to showing that the role of education in universities still plays a significant role in the formation of students' self that encourages the emergence of entrepreneurship among undergraduate graduates. Therefore, the formation of programs and a combination of practical training and an entrepreneurial climate at the higher education level need to be a concern for the development of entrepreneurship in developing countries. Keywords: University Entrepreneurship Support; Subjective Norms; Attitudes; Self-Efficacy; Entrepreneurial Intentions